Dental pathology and diet of the population of yuthu (400 - 100 BC) in the formative period of Cusco, Peru - Ricalde Pino, Angela Silvia (2021)
In a Funerary context, the human remains that have better state of conservation over time and from which most information can be obtained related to the lifestyle, pathological processes, feeding habits, oral health profiles, inmunity and cultural practices, of an individual, are the bones and teeth. The present interdisciplinary analysis, reveals the precarious oral health and paleopathology that affected these individuals, which allowed to identify, for this región of Peru, the first reports and evolution of dental paleopathology that until now have been affecting humanity.